Surface design for fabric - Irwin, Kimberly A (Fairchild Books, an imprint of Bloomsbury Publishing Inc., 2015)
"Surface Design for Fabric is a comprehensive, how-to guide to more than 60 surface design techniques for various fabrics and leather--ranging from traditional to experimental. Clear, step-by-step instructions and photographs demonstrate surface design techniques, allowing readers to quickly grasp the material and further explore and experiment on their own. Irwin covers a broad range of surface design techniques including: dyeing, staining, removing color, resists, printing and transfer, fiber manipulation, fabric manipulations, embroidery, and embellishments. Each chapter begins with a brief description and historical overview of the technique, and includes a fabric selection quick guide, tools and materials, how to set up your workspace, application methods and safety guidelines for each technique. Photographs and designer biographies showcase surface design techniques used in real-world designs. The final chapter offers advice on how to combine techniques to create commercial and avant-garde surface design. This modern studio resource clearly guides readers in the creation of beautiful, innovative, and professional surface designs"-- Provided by publisher.